Social Capital and the Sustainability of Silk-Weaving Enterprises: Trust, Norms, and Networks in Pakkanna Village, Wajo Regency - hajar, muhammad; syukur, muhammad; nurdin, ibrahim; said, m. ridwan; nasuhan, najamuddin (Tamaddun Life, 2025)
This qualitative study investigates the role of social capital specifically trust, community norms, and social networks in sustaining household silk-weaving enterprises in Pakkanna Village, Wajo Regency, South Sulawesi, Indonesia. Employing a case-study approach with in-depth interviews, observations, and document analysis, the research identifies trust as a critical informal governance mechanism, significantly reducing transaction costs and streamlining production processes. However, reliance on trust also reinforces asymmetric power relationships, where collectors dominate market interactions, constraining artisans' bargaining power. Additionally, community norms such as mutual help (gotong-royong) and meticulous craftsmanship (mappasile) maintain high product quality and preserve cultural identity but simultaneously restrict innovation and responsiveness to market changes. Social networks enhance access to resources, information, and markets, yet the artisans’ dependency on collectors limits their direct market engagement, highlighting inherent vulnerabilities. External interventions through digital platforms and government programs show potential but face generational resistance and uneven uptake. Practical implications suggest promoting diversified market strategies and targeted interventions to strengthen artisans’ positions, while theoretical implications call for integrating gender and power dynamics into social-capital frameworks. Policy recommendations advocate combining infrastructural support with capacity-building and implementing geographic indications to secure cultural authenticity and economic sustainability.